A obra o romance do pavão misterioso como metodologia de ensino e aprendizagem - um manual para o/a professor/a - Barbosa, Geóstenys de Melo (2023)
This research investigates the cordel literature as a pedagogical support in art classes. Its main objective is the creation of a Guidance Manual for Art teachers, based on work developed with students from the 9th grade classes of fundamental education II, from the public school Marlene Alves de Mendes, in the city of Pilõezinhos, in Paraíba, using the Cordel “O Romance do Pavão Mysteriozo”, by José Camelo de Melo Rezende. This work also aims to promote local art, valuing popular culture and reaffirming the importance of this literary genre that is the cordel brochures. This study/experience was developed by researching the cordel literature genre, the woodcut technique, the characters from the stories and the cultural value of the cordel. It is a participatory research, with a qualitative approach, that analyzed the results from the art workshops planned in its didactic-pedagogical intervention actions. This investigation also emphasizes the importance of working with popular culture in the classroom using the stories from the cordel brochures, enabling the students to critically reflect and artistically practice, allowing them to see and interpret the world through their experiences, contributing with the teaching and learning process in artistic practices in the classroom.